If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5v + -5 = 19v + 11 Reorder the terms: -5 + 5v = 19v + 11 Reorder the terms: -5 + 5v = 11 + 19v Solving -5 + 5v = 11 + 19v Solving for variable 'v'. Move all terms containing v to the left, all other terms to the right. Add '-19v' to each side of the equation. -5 + 5v + -19v = 11 + 19v + -19v Combine like terms: 5v + -19v = -14v -5 + -14v = 11 + 19v + -19v Combine like terms: 19v + -19v = 0 -5 + -14v = 11 + 0 -5 + -14v = 11 Add '5' to each side of the equation. -5 + 5 + -14v = 11 + 5 Combine like terms: -5 + 5 = 0 0 + -14v = 11 + 5 -14v = 11 + 5 Combine like terms: 11 + 5 = 16 -14v = 16 Divide each side by '-14'. v = -1.142857143 Simplifying v = -1.142857143
| 3ln(x-1)=0 | | (-4x-2)-(-5)= | | 61+p=180+-65 | | (8+2x)*(10+2x)= | | 16p+24= | | 18m-14=13m+2 | | (8+2x)*(10+2x)=168 | | 36x^3-6x= | | 5+35x=28+14 | | 4x^2=-2x+2 | | 26p-24= | | ln(x)=ln(x+1)-ln(2) | | 6(2x-15)=3(5x-30) | | ln(y-25)=5x | | 18x+4+4x=25+8x+7 | | s^2=40 | | 3a+11=20 | | -6w-3(-2x+6w)-5x= | | -6x+x^2-16=0 | | 4x-4=14-114 | | (e^4(x))=1 | | (e^4x)-1=0 | | 7500.00+155.00x=7500.00 | | e^4x-1=0 | | (6x+4)7= | | 2(3-3h)-6(h+2)= | | 3(x+4)-7=5x+11 | | (9x-4)=(4x+2) | | 3x-12=2x-10 | | (18z+3)+32=23z | | 4(y-1)=8 | | (y+7)5-7-(y-4)=3(9-y)+5 |